Understanding the Ecology of Artificial Reefs: No Simple Answers - Bill Lindberg; Mark Schrope (EDIS, 2010)
SGEB65, a 4-page illustrated article by Bill Lindberg and Mark Schrope, discusses the ecological impacts of artificial reefs and implications for conservation in interview format. Published by the UF Florida Sea Grant Program, January 2010.